2016
DOI: 10.1242/jcs.194605
|View full text |Cite
|
Sign up to set email alerts
|

Flow-dependent myosin recruitment during Drosophila cellularization requires zygotic dunk activity

Abstract: Actomyosin contractility underlies force generation in morphogenesis ranging from cytokinesis to epithelial extension or invagination. In Drosophila, the cleavage of the syncytial blastoderm is initiated by an actomyosin network at the base of membrane furrows that invaginate from the surface of the embryo. It remains unclear how this network forms and how it affects tissue mechanics. Here, we show that during Drosophila cleavage, myosin recruitment to the cleavage furrows proceeds in temporally distinct phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
3
8
0
Order By: Relevance
“…Since Sqh-mCherry marked the furrow tip, it was also used to estimate furrow lengths during cellularization. The dynamics of furrow length increase in the slow and fast phase in GRAF-OE were similar to controls during cellularization (Figure 6-figure supplement 1A) (Figard et al, 2013;He et al, 2016;Lecuit and Wieschaus, 2000;Merrill et al, 1988;Royou et al, 2004;Warn and Magrath, 1983). In contrast, the slow phase in Graf CR57 was extended and the fast phase started at a later time point (Figure 6-figure supplement 1A).…”
Section: Graf Depletion and Overexpression Leads To Changes In Myosin II Distribution At The Contractile Ring During Cellularizationsupporting
confidence: 53%
See 2 more Smart Citations
“…Since Sqh-mCherry marked the furrow tip, it was also used to estimate furrow lengths during cellularization. The dynamics of furrow length increase in the slow and fast phase in GRAF-OE were similar to controls during cellularization (Figure 6-figure supplement 1A) (Figard et al, 2013;He et al, 2016;Lecuit and Wieschaus, 2000;Merrill et al, 1988;Royou et al, 2004;Warn and Magrath, 1983). In contrast, the slow phase in Graf CR57 was extended and the fast phase started at a later time point (Figure 6-figure supplement 1A).…”
Section: Graf Depletion and Overexpression Leads To Changes In Myosin II Distribution At The Contractile Ring During Cellularizationsupporting
confidence: 53%
“…Drosophila cellularization occurs by plasma membrane furrow extension between adjacent nuclei from 3 μm to 40 μm in approximately 45 min at 25 o C (He et al, 2016).…”
Section: Graf Depletion Leads To Premature Constriction In Early Cellularization and Hyper Constriction In Mid And Late Cellularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, in early Drosophila development, nuclear division and mitosis during syncytial division take <2 min. The redistribution of actomyosin to the site of incipient cellularization furrow invagination occurs over ∼14 min (18). During gastrulation, mesoderm apical constriction (which precedes ventral furrow invagination) completes in about 10 min (15).…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent electron microscopy showed that the apical membrane is initially rich with microvilli that flatten as cellularization progresses. Both endocytosis and mechanical unfolding of these microvilli have been proposed to drive this change in apical membrane topology (Fabrowski et al, 2013;Figard et al, 2013;Figard et al, 2016;He et al, 2016). Other evidence suggests that Rab8 facilitates directed exocytosis to lateral membrane faces, allowing endosomal membrane to be added to these growing membrane faces (Mavor et al, 2016).…”
Section: Transcytosis As a Regulator Of Epithelial Cell Shape And Tubulogenesismentioning
confidence: 99%